Study on magnetic abrasive finishing combined with electrolytic process. (31st July 2019) - Sun, Xu; Zou, Yanhua
To improve polishing efficiency of traditional magnetic abrasive finishing (MAF) for polishing metal material, we proposed an effective MAF which combined with electrolytic process. The hardness of workpiece surface can be reduced since passive films are generated by electrolytic action. Simultaneously, the generated passive films can be easily removed by friction which is generated between magnetic particles and workpiece. Therefore, electrolytic magnetic abrasive finishing (EMAF) can significantly minimise the surface roughness in a shorter finishing time. In this study, we focused on researching the combination of the first finishing step (EMAF step) time and second finishing step (MAF step) time. The optimal experimental results showed that the surface roughness R a can be reduced to less than 30 nm at 4 min EMAF step, the surface roughness R a can be reduced to 20 nm at 10 min MAF step. Furthermore, we also analysed the change in size of mixed magnetic abrasive.